Strength characteristics and marginal sealing ability of chlorhexidine-modified glass ionomer cement: An in vitro study - P Ahluwalia; S Chopra; A M Thomas (Wolters Kluwer Medknow Publications, 2012)
Background: This study was done to compare and evaluate the compressive strength, diametral tensile strength, and microleakage of glass ionomer cement and chlorhexidine-modified glass ionomer cement. The glass ionomer cements used in the study were Fuji IX for group I and chlorhexidine-modified glass ionomer cement for group II. Materials and Methods: The strength characteristics (compressive and diametral tensile strengths) and microleakage of both the groups were evaluated after 24 h. Student's "t" test and Mann-Whitney test were used for statistical analysis of the difference in strength characteristics and microleakage. Results: There was no statistical difference (P>0.05) in the strength characteristics and microleakage of glass ionomer cement and chlorhexidine-modified glass ionomer cement. Conclusion: The present study suggests that strength characteristics and marginal sealing capability of chlorhexidine-modified glass ionomer cement were similar to those of glass ionomer cement (Fuji IX). So, chlorhexidine-modified glass ionomer can be considered as a substitute for glass ionomer cements, especially in pediatric dentistry.